2006
DOI: 10.2478/s11756-006-0086-9
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and dispersal of mites (Acari, Mesostigmata) in nests of the white stork (Ciconia ciconia)

Abstract: The fauna of Mesostigmata in nests of the white stork Ciconia ciconia was studied in the vicinity of Poznań (Poland). A total of 37 mite species was recovered from 11 of the 12 nests examined. The mite fauna was dominated by the family Macrochelidae. Macrocheles merdarius was the most abundant species, comprising 56% of all mites recovered. Most of the abundant mite species were associated with dung and coprophilous insects. It is likely that they were introduced into the nests by adult storks with dung as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 4 publications
1
33
1
4
Order By: Relevance
“…Macrocheles ancyleus has often been found in perennial nests of birds of prey (Gwiazdowicz et al 1999(Gwiazdowicz et al , 2000 and the black stork (B loszyk et al 2009), and it was also present in nests of the white stork Bajerlein et al 2006;), but only three specimens were found in this study. On the other hand, Poecilochirus austroasiaticus is typically associated with carrion (Korn 1983), and is carried phoretically by necrophilous beetles of the genus Nicrophorus.…”
Section: Comparison With Other Species Of Birdscontrasting
confidence: 44%
See 1 more Smart Citation
“…Macrocheles ancyleus has often been found in perennial nests of birds of prey (Gwiazdowicz et al 1999(Gwiazdowicz et al , 2000 and the black stork (B loszyk et al 2009), and it was also present in nests of the white stork Bajerlein et al 2006;), but only three specimens were found in this study. On the other hand, Poecilochirus austroasiaticus is typically associated with carrion (Korn 1983), and is carried phoretically by necrophilous beetles of the genus Nicrophorus.…”
Section: Comparison With Other Species Of Birdscontrasting
confidence: 44%
“…The most abundant component of this associated fauna are arthropods, especially mites. Many birds build nests that last only for a single season, but the large perennial nests made by birds of prey and other birds such as storks allow the development of mite communities of definite structure and species composition (Philips 1981;Gwiazdowicz 2003a, b;Gwiazdowicz et al 1999Gwiazdowicz et al , 2000Gwiazdowicz et al , 2005Gwiazdowicz et al , 2006Bajerlein et al 2006;B loszyk et al 2005Krištofik et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This predatory European mite species has been recorded in manure, compost and decomposing litter (Hirschmann & Wiśniewski 1982) and is also found in bird nests, e.g., white stork Bajerlein et al 2006) and the white-tailed eagle .…”
Section: Resultsmentioning
confidence: 99%
“…It is often found in dung, either fresh and wet or old and dry, and is also found in bird nests, including those of the common blackbird Turdus merula L., 1758 (Mašán 2003), and the white stork Bajerlein et al 2006). Macrocheles ancyleus Krauss, 1970 (Macrochelidae) was described from a rotting log, but appears to have a strong affinity for bird nests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation